Wear behavior and morphologic characterization of diamond segments induced by crystal plane characteristics of diamond grits in sawing hard materials. (February 2022) - Sun, Depeng; Zhang, Heng; Cai, Yu; Sun, Tongyan; Zhang, Jinsheng
Abstract: The wear of diamond grains (DGs) is a classic problem, affects the final cost, in sawing hard materials (granitic rocks) for slabs. However, the previous research rarely pays attention to study the wear of DGs considering the crystal plane characteristics. Hence, in this study, the aim is to explain the fracture morphology of DGs in sawing granitic rocks taking into account the crystal plane characteristics. The wear experiment was carried out with a frame saw. Then the surface morphology of DGs was characterized by scanning electron microscope (SEM). According to wear characteristics of DGs, the wear of DGs was divided into seven different types, including fresh, whole, micro fractured, pulled-out, flush with matrix, macro fractured and blunt. Interestingly, the bottom surface of the pulled-out DGs in contact with the matrix was mostly {100} crystal planes that account for approximately 80%. In addition, flush with matrix mostly occurred on the {111} crystal planes (account for 90%), and mostly at both ends of the diamond segments (DSs). Then, this phenomenon is explained by the interplanar spacing of DGs. Moreover, wear behavior and morphologic characterization of DGs were discussed considering the factors of stone sawing (e.g., detritus) and the characteristics of DGs (e.g., dislocation). Finally, wear evolution mechanism of DSs topography were proposed. This research enhances to deeply understand the wear of DGs in granite processing and provides guidance for the design of DSs. Highlights: There are obviously more micro-cracks on the {111} than the {100} crystal plane. Fracture plane with {111} crystal plane is approximately 90% due to the relatively higher interplanar spacing. The wear evolution mechanism of diamond segments topography were proposed.